Retrieval of Gallbladder Via Umbilical Versus Epigastric Port Site During Laparoscopic Cholecystectomy: A Systematic Review and Meta-Analysis. Issue 5 (October 2019) - Hajibandeh, Shahin; Hajibandeh, Shahab; Clark, Matthew C.; Barratt, Owain A.; Taktak, Samih; Subar, Daren; Henley, Natasha
Abstract : Objective: The objective of this study was to evaluate the comparative efficacy of gallbladder retrieval via the epigastric and umbilical port during laparoscopic cholecystectomy. Methods: We systematically searched MEDLINE, EMBASE, CINAHL, CENTRAL, the World Health Organization International Clinical Trials Registry, ClinicalTrials.gov, ISRCTN Register, and bibliographic reference lists. Postoperative pain intensity, port-site infection, hernia, bleeding, and retrieval time were outcome parameters. Combined overall effect sizes were calculated using fixed-effect or random-effects models. Results: We identified 5 randomized controlled trials and 1 prospective cohort study reporting a total of 2394 patients who underwent laparoscopic cholecystectomy with retrieval of the gallbladder via the umbilical port (n=1194) or epigastric port (n=1200). Our initial analysis demonstrated that gallbladder retrieval via the umbilical port was associated with a nonsignificant reduction in pain assessed by visual analogue scale at 24 hours [mean difference (MD): −0.49, 95% confidence interval (CI): −1.06 to 0.08, P =0.09] compared with the epigastric port. However, after sensitivity analysis and eliminating the source of heterogeneity, it reached statistical significance (MD: −0.66, 95% CI: −0.85 to −0.48, P <0.00001). Moreover, gallbladder retrieval via the umbilical port was associated with significantly shorter retrieval time (MD: −1.83, 95% CI: −3.18 to −0.49, P =0.008) but similar risk of port-site infection (odds ratio: 1.99, 95% CI: 0.53-7.44, P =0.31) and hernia (odds ratio: 0.33, 95% CI: 0.03-3.20, P =0.34). Conclusions: Our analysis demonstrated that retrieval of the gallbladder via the umbilical port may be associated with less postoperative pain in patients undergoing laparoscopic cholecystectomy compared with epigastric port retrieval. It may also be associated with shorter gallbladder retrieval time. However, the available evidence is limited. Abstract : Supplemental Digital Content is available in the text.